Implementasi Dimensi Bernalar Kritis pada Projek Penguatan Profil Pelajar Pancasila - Hakim Palembani, Abdul; Febrieanitha Putri , Yecha; Marlina, Leny; Dewi, Kurnia; Febriyanti, Febriyanti (Green Publisher Indonesia, 2025)
This study aims to determine the implementation of the critical reasoning dimension in the project to strengthen the profile of Pancasila students at Kindergarten Negeri Pembina 4 Palembang. The research method used is a qualitative method with a phenomenological approach. Data collection techniques through observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The results of the study show that the implementation of the critical reasoning dimension in the project to strengthen the Pancasila student profile at Pembina 4 Palembang State Kindergarten has been carried out in line with the learning objectives in the teaching module to foster early childhood critical reasoning skills. This is evidenced by exploration activities, such as making jumputan fabric, they not only learn but also understand the concept related to making jumputan fabric. There are supporting factors that contribute positively to the availability of adequate resources and infrastructure that facilitate the learning process, in addition to the enthusiasm and enthusiasm shown by the children during this exciting activity. The inhibiting factor is the lack of understanding of teachers about the Pancasila student profile. However, with module training that focuses on the Pancasila student profile by the principal, it can improve teachers' understanding.